Optimal Period for Iodine Supplementation in Diet on Growth Performance, Carcass Composition and Chemical Compositions of Tilapia (Oreochromis niloticus) - Sangsalasri, Chanida; Songserm, Ornprapun; Rattanatabtimtong, Sukanya; Ingthamjit, Suchart (Journal of Mahanakorn Veterinary Medicine, 2020)
Increasing iodine level in freshwater fish is an alternative to increase the nutritional value of flesh and reduce iodine deficiency problems in Thai population. The objective of the research is to study on optimal period for iodine supplementation in diet on growth performance, carcass composition and chemical composition of tilapia (Oreochromisniloticus). One thousand and two hundred tilapia with the average weight of 90 g/fish were randomly divided into 4 groups with 3 replications. One hundred fish replicate were raised in a cage in the earthen pond for a period of 120 days. All groups of tilapia received the following diets: Group 1 commercial fish floating diet with at least 30% protein and the average amount of iodine is 3.53 mg/kg. Group 2-4 received diet supplemented with potassium iodate (KIO3) 30 mg/kg at different periods (60, 30 and 15 days prior to the end of the experiment). The experiment was conducted with completely randomized design (CRD). The results found that growth performance, carcass composition and chemical composition of tilapia were not significantly differences (P>0.05). Fish that received iodine supplementation at 60, 30 and 15 days prior to the end of the experiment had doubled flesh iodine content comparing to fish without iodine supplementation (P<0.01), while flesh iodine content of the other groups were not significantly differences (P>0.05). Therefore, providing iodine supplemented diet for 15 days before harvesting is optimal for increasing the amount of iodine in tilapia flesh.